2001
DOI: 10.1177/1358836x0100600206
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors associated with endothelial dysfunction affect the early onset of coronary artery disease in Korean males

Abstract: Abstract:The maintenance of balance between nitric oxide (NO) and the superoxide anion is required for proper functioning of the endothelium. To investigate the relationship between genetic factors associated with endothelial function and the development of coronary artery disease (CAD), endothelial nitric oxide synthase (ecNOS) gene a/b polymorphism and NADH/NADPH oxidase p22 phox gene C242T polymorphism were examined in 305 Korean male CAD patients and 215 healthy male control subjects. The ␤-fibrinogen gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
(34 reference statements)
0
25
0
2
Order By: Relevance
“…Of the 16, 9 showed an increased risk in individuals homozygous for the a allele compared with b allele carriers (b/b plus b/a), 10,11,35,38,39,41,[43][44][45] but only 1 was statistically significant 43 (Figure 3). With a fixed-effect model, the summary OR for IHD among homozygotes for the intron-4a allele was 1.34 (95% CI, 1.03 to 1.75; Pϭ0.03) (Figure 3).…”
Section: Intron-4 and Ihdmentioning
confidence: 99%
“…Of the 16, 9 showed an increased risk in individuals homozygous for the a allele compared with b allele carriers (b/b plus b/a), 10,11,35,38,39,41,[43][44][45] but only 1 was statistically significant 43 (Figure 3). With a fixed-effect model, the summary OR for IHD among homozygotes for the intron-4a allele was 1.34 (95% CI, 1.03 to 1.75; Pϭ0.03) (Figure 3).…”
Section: Intron-4 and Ihdmentioning
confidence: 99%
“…Yoon et al (42) also identified an association of this polymorphism with the risk (20) suggested that enoS polyporphism was significantly associated with the development of CAD in Korea. An interesting aspect of the results from our study is that they conflict with a study of the same gene polymorphism performed in a different part of turkey (23).…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47][48] The ecNOS gene a/b polymorphism and the β-Nicotinamide adenine dinucleotide/nicotinamide adenine dinucleotide phosphate (NADH/NADPH) oxidase p22 phox gene C242T polymorphism are found to be significantly associated with the development of CAD. 45,46 Regarding this topic, the following reduce NO bioavailability: polymorphisms in the eNOS gene, 47 upregulation of matrix metalloproteinase-2,49 and elevated levels of dimethylarginine, which is a competitive antagonist of endothelial nitric oxide synthase (eNOS). Some studies also found microRNA 217 upregulation, an NAD-dependent deacetylase, as responsible for endothelial alteration and eNOS activity decrease.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32] Experimental and clinical studies have provided new data about the mechanisms of specific aspects of endothelial function, therefore a potential mechanism of endothelial dysfunction is alteration of the signaling mechanisms involved in eNOS activation. 45 Some novel approaches in patients with polymorphisms or mutations of genes that might play a pathogenic role in endothelial dysfunction investigate the relationship between genetic factors associated with endothelial function and the development of cardiac alterations. [45][46][47][48] The ecNOS gene a/b polymorphism and the β-Nicotinamide adenine dinucleotide/nicotinamide adenine dinucleotide phosphate (NADH/NADPH) oxidase p22 phox gene C242T polymorphism are found to be significantly associated with the development of CAD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation